Implementing specialist psychological support for caregivers in psychosis services: a preliminary report*. Issue 2 (3rd April 2017) - Smallwood, Jane; Jolley, Suzanne; Makhijani, Jyotsna; Grice, Sarah; O'Donoghue, Emma; Bendon, Paula; Greenaway, Liz P.; Onwumere, Juliana
Abstract: Background : Research demonstrates the importance of supporting caregivers of people with psychosis, but routine implementation studies are lacking. We evaluate a newly-developed caregiver support service, offering individual and group psychoeducation, practical advice and emotional support, working alongside usual community mental health provision for people with established psychosis. Aims : We aimed to provide analysis of preliminary data on the rate and suitability of referrals, engagement, and helpfulness, to inform future larger-scale implementation and evaluation. Method : We conducted a mixed-methods audit during the service's first ten operational months (01 September 2013–30 June 2014). Caregivers gave qualitative feedback and completed measures of the impact of caregiving pre- and post-intervention. Results : Referrals totalled 103 (10/month), with 45 (44%) initial meetings; and 28 (27%) individual interventions (≥1 sessions, mode = 3). Caregivers were predominantly black British/African/Caribbean parents. Self-reported needs and caregiving experiences were consistent with the literature. Two-thirds of caregivers were clinically distressed. Qualitative feedback showed that caregivers valued the service. Outcomes suggest improved experiences of caregiving following intervention. Conclusions : Findings highlight the potential benefits and challenges of routinely providing psychologically-focused caregiver support. Limitations and future plans are discussed.